11C-Choline and 18F-FDG PET/CT in the Detection of Occult Prostate Cancer in the Context of a Paraneoplastic Syndrome. (August 2015) - Jiménez-Bonilla, Julio; Quirce, Remedios; Banzo, Ignacio; Martínez-Rodríguez, Isabel; Carril, José Manuel
Abstract : Abstract: In a 73-year-old man, an occult neoplasm was suspected after 2 consecutive deep venous thrombosis, the latter under anticoagulant therapy and previous axonopathy. After normal CT and MRI findings, a requested 18 F-FDG PET/CT showed a focal uptake in the prostate. Because FDG uptake in the prostate is infrequent, a 11 C-choline PET/CT was indicated revealing a focal uptake in the same location. No other abnormalities were detected in the rest of the body. A guided biopsy by ultrasonography was performed revealing a prostate carcinoma and inflammation in both prostatic lobes.